Hexabenzocoronene Graphitic Nanocoils Appended with Crown Ethers: Supramolecular Chirality Induced by Host–Guest Interaction. Issue 72 (21st November 2019) - Zeng, Wang; Zhang, Wei; Li, Xianying; Jin, Wusong; Zhang, Dengqing
Abstract: We have designed and synthesized two new achiral hexa‐ peri ‐hexabenzocoronene (HBC) derivatives, HBC CE and HBC TEG‐CE, which bear the crown ether as the pendant for the amino acid binding site. The HBC CE self‐assembled into a racemic mixture of P ‐ and M ‐handed helical nanocoils, however, in the presence of chiral amino acid guests, it formed helical nanocoils with one‐handed screw sense. The effects of the concentration, type and configuration of the guests on the induced circular dichroism (ICD) during the co‐assembly of HBC CE with chiral amino acids were also investigated. Additionally, after complete removal of the chiral guests, the optically active nanocoils did not racemize, even in the presence of excess amino acids with the opposite configuration. In contrast, HBC TEG‐CE with a long triethylene glycol (TEG) chain between the crown ether group and the HBC unit did not exhibit ICD during the co‐assembly with chiral amino acids. Abstract : Spiral tap : In this work, a simple and commercially available amino acid was used as chiral source for the noncovalent assembly of a hexabenzocoronene derivative, HBC CE, to produce a helix sense‐selective and helical memory nanocoiled architecture (see graphic).